Gastric bypass in morbid obese patients is associated with reduction in adipose tissue inflammation via N-oleoylethanolamide (OEA)-mediated pathways - Montecucco, Fabrizio; Lenglet, Sébastien; Quercioli, Alessandra; Burger, Fabienne; Thomas, Aurélien; Lauer, Estelle; Silva, Analina Raquel da; Mach, François; Vuilleumier, Nicolas; Bobbioni-Harsch, Elisabetta; Golay, Alain; Schindler, Thomas H.; Pataky, Zoltan (Thrombosis and Haemostasis, 2015)
Paradoxically, morbid obesity was suggested to protect from cardiovascular co-morbidities as compared to overweight/obese patients. We hypothesise that this paradox could be inferred to modulation ofthe “endocannabinoid” system on systemic and subcutaneous adipose tissue (SAT) inflammation. We designed a translational project including clinical and in vitro studies at Geneva University Hospital. Morbid obese subjects (n=11) were submitted to gastric bypass surgery (GBS) and followed up for one year (post-GBS). Insulin resistance and circulating and SAT levels of endocannabinoids, adipocytokines and CC chemokines were assessed pre- and post-GBS and compared to a control group of normal and overweight subjects (CTL) (n=20). In vitro cultures with 3T3-L1 adipocytes were used to validate findings from clinical results. Morbid obese subjects had baseline lower insulin sensitivity and higher hs-CRP, leptin, CCL5 and anandamide (AEA) levels as compared to CTL. GBS induced a massive weight and fat mass loss, improved insulin sensitivity and lipid profile, decreased C-reactive protein, leptin, and CCL2 levels. In SAT, increased expression of resistin, CCL2, CCL5 and tumour necrosis factor and reduced MGLL were shown in morbid obese patients pre-GBS when compared to CTL. GBS increased all endocannabinoids and reduced adipocytokines and CC chemokines. In morbid obese SAT, inverse correlations independent of body mass index were shown between palmitoylethanolamide (PEA) and N-oleoylethanolamide (OEA) levels and inflammatory molecules. In vitro, OEA inhibited CCL2 secretion from adipocytes via ERK1/2 activation. In conclusion, GBS was associated with relevant clinical, metabolic and inflammatory improvements, increasing endocannabinoid levels in SAT. OEA directly reduced CCL2 secretion via ERK1/2 activation in adipocytes.
Keywords: Endocannabinoids; obesity; subcutaneous adipose tissue; chemokine